Using songs in teaching English. (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
Songs play an important role in the development of young children learning a second language. This paper begins by looking at why songs can be considered valuable pedagogical tools. In particular, it will discuss how songs can help learners improve their listening skills and pronunciation, and how they can be useful in the teaching of vocabulary and sentence structures. It will be also discussed how songs an reflect culture and increase students’ overall enjoyment of learning a second language.